The impact of creatine supplementation on renal function: A case report and literature review - Antonio Villa; Lucia Trotta; Giovanni Faraci (Advances in Medicine, Psychology, and Public Health)
Creatine supplementation is one of the most widely used dietary supplements worldwide, yet its potential adverse effects on kidney function remain a concern. We report a case of a 25-year-old man who presented with symptoms of left renal colic and exhibited a temporary elevation in serum creatinine levels following oral intake of 10 grams of creatine. Laboratory tests showed elevated serum creatinine (2.12 mg/dL) and urea (45 mg/dL), with an estimated creatinine clearance of 60.3 ml/min. After analgesic and antispastic treatment, the patient's symptoms resolved, and subsequent follow-up indicated normalization of renal function parameters. While several longitudinal, controlled studies on the adverse effects of exogenous creatine supplementation have been published, no evidence of kidney function deterioration has been observed in healthy subjects. Creatine supplementation can alter serum creatinine levels, potentially serving as a false indicator of kidney injury. In this case, we believe the observed increase in creatinine levels was a transient effect of exogenous creatine intake without any actual impairment of renal function.